Developing Ideal Leadership Perception of Accounting Students Through The 360 Degrees Leadership Education - Hanny Hanny; Nunik Lestari Dewi; Sinta Setiana; Meliana Halim (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
This study aims to determine the effect of 360 Degree Leadership Education on the perception of Accounting Students about the ideal leadership principles and to analyze the difference of the Accounting student’s leadership perception before and after got this education. We hope that this study can contribute to support the Accounting Profession to have the professional Accountants who deserve to lead this profession in time to come. The research data were obtained through some questionnaires that have been distributed to 100 students who haven’t got the 360 Degree Leadership Education and 100 other students who have got it in 2019. We used Non-Probability Sampling with the Purposive Sampling Method to get representative sample. We also used the descriptive analysis, Simple Linear Regression, and the comparative hypothesis testing to test the hypothesis. The results show that the 360 Degree Leadership Education influences the leadership perception of the Accounting students by 27.5%. This research indicates that there is different leadership perception between these two groups of students. Furthermore, it shows that the Accounting student who haven’t got the 360 Degree Leadership Course tend to agree with the myth of leadership while the other students who have got it show the opposite tendency. Keywords: 360 Degree Leadership Education; Leadership Perception; Accounting Students.